2017
DOI: 10.5195/jyd.2016.469
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Structured Experiences during Youth Programs: Development of Brief Measures of Perceived Value and Engagement

Abstract: A brief questionnaire that can be used to routinely monitor the quality of structured experiences for youth is discussed in this paper. Structured experiences are discrete periods of time in which youth gather for activity under the supervision of adult or youth leaders. Four-item measures of perceived value and engagement were created. A questionnaire including these measures along with items from the 4-H Common Measures was administered to 219 youth from 11 4-H clubs. Data were analyzed for evidence of relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…A previous study found acceptable alpha reliability of .71 (Ellis, Taggart, et al, 2017). The alpha reliability estimate for the scale during this study was acceptable at .67.…”
Section: Overall Camp Engagementsupporting
confidence: 50%
“…A previous study found acceptable alpha reliability of .71 (Ellis, Taggart, et al, 2017). The alpha reliability estimate for the scale during this study was acceptable at .67.…”
Section: Overall Camp Engagementsupporting
confidence: 50%
“…Evidence of validity is also present. The measure of perceived value of time spent has produced positive correlations with perceptions of safety and support in youth settings, as well as three indicators of the quality of structured youth experiences: engagement, meaningfulness, and satisfaction (Ellis et al, 2016). The alpha reliability estimate for the current study was .94.…”
Section: Perceived Value Of Time Spentmentioning
confidence: 64%
“…Perceived value of time spent is defined as "the individual's degree of contentment with her or his decision to participate in the structured experience" (Ellis, Taggart, Martz, Lepley, & Jamal, 2016). Five items were included on the questionnaire: Reliability coefficients of .82 (Ellis et al, 2016) and .93 (Taggart, 2017) were previously reported. Evidence of validity is also present.…”
Section: Perceived Value Of Time Spentmentioning
confidence: 99%
“…Meaningfulness has been defined as "the extent to which the structured experience yielded active thought about something learned during that experience" (Ellis et al, 2016, p. 7). This TSE operationalization of meaningfulness has been used to evaluate an approach for classifying the effectiveness of 4-H meetings (Ellis et al, 2016). Meetings high in both engagement and perceived value of time spent are classified as "positive youth development" meetings.…”
Section: Meaningfulnessmentioning
confidence: 99%
“…Meaningfulness scores for "positive youth development" meetings were significantly higher than meetings classified as "hedonic," "instrumental," or "unproductive." Perceived value of time spent refers to the individuals' degree of contentment with her or his decision to commit time and personal resources to participate in the structured experience (Ellis et al, 2016). Perceived value has been studied extensively in the business and tourism literature (e.g., Petrick, 2002;Zeithaml, 1988), but those constructions of perceived value focus on the financial value of specific product or activity features.…”
Section: Meaningfulnessmentioning
confidence: 99%